GST AS A TOOL FOR ECONOMIC GROWTH IN INDIA: A STUDY - Narasagondar, Manjunath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
he Goods and Services Tax (GST), implemented on July 1, 2017, is one of India’s most significant tax reforms, aimed at unifying the country’s complex indirect tax system. By replacing multiple indirect taxes like excise duty, VAT, service tax, and entry tax, GST has streamlined taxation, eliminated the cascading effect, and created a single national market. This paper explores how GST has acted as a catalyst for economic growth by improving tax compliance, enhancing ease of doing business, and boosting government revenue collection. One of the key advantages of GST is its role in reducing tax inefficiencies and simplifying compliance through a digitalized tax-filing system. The introduction of the input tax credit (ITC) has lowered production costs, making Indian goods and services more competitive in both domestic and international markets. Furthermore, by removing state barriers, GST has significantly improved logistics efficiency, reducing transportation costs and boosting sectors like manufacturing, e-commerce, and retail. The paper also examines the impact of GST on small and medium enterprises (SMEs), which have faced both challenges and benefits. While the compliance burden initially posed difficulties, the long-term advantages of GST, such as increased market accessibility and lower tax burdens under the composition scheme, have fostered business expansion. Additionally, GST has played a crucial role in formalizing the economy, increasing tax collection, and providing the government with higher revenues for infrastructure development and social programs. Despite initial challenges, including frequent rate changes and compliance hurdles, GST continues to evolve as a growth-oriented tax reform. Overall, GST has contributed to economic stability, higher GDP growth, and a more transparent tax system, making India an attractive destination for investors and businesses, further driving national economic progress.